LITERATURE REVIEW OF EMOTIONAL INTELLIGENCE AND PSYCHOLOGICAL WELL-BEING - Siti Hajar Muhammad Syafiq Tan; Noor Hafikah Othman; Nur Izzati Syahirah Mohd Salleh; Puteri Adriana Zakirah Mohd Azri; Nur Aqilah Adeline Badarul Hissam; Syahrina Hayati Md Jani (International Journal of Accounting, Finance and Business, 2022)
This paper reviews the idea of emotional intelligence and terms such as intelligence,emotion, and emotional intelligence. A distinction will be made between the various theories ofemotional intelligence, the one that emphasises mental ability from those that mix mentalcapabilities with personal traits. This paper claims that Mayer and Salovey’s definition ofemotional intelligence is appropriate to be a model that can explain emotional intelligenceamong adolescents. Emotional intelligence as the capability to understand and control one’semotions is an ability that can be learned and enhanced where the level of an individual’semotional competence increases with age. Next, the purpose of this review is to reveal theexisting literature on the definition as well as the relationship of emotional intelligence andpsychological well-being. Specifically, this paper reviews the literature on the relationshipbetween emotional intelligence and psychological well-being; relationship between emotionalintelligence and perceived social support; and relationship between emotional intelligence andperceived stress. The review will give a holistic understanding of the emotional intelligence,psychological well-being, perceived social support, and perceived stress concepts for futureresearchers and aid to identify the research gap.